Analysis of Connotative Meaning as an Element of Dramatization in the Film Gowok: Javanese Kamasutra - Tia Permata Sari; Mufidatuz Zahro Aj-Jauharoh; Dodi Firmansyah; Dase Erwin Juansah; Mulya Tiara Fauziah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to uncover connotative meanings as elements that construct the dramatization in the Gowok: Kamasutra Jawa Indonesia movie. This movie depicts the complex cultural values of Java through the conflict between love, social status, and morality. The method used is descriptive qualitative with the listen-and-note technique, where data is obtained from the characters' utterances that contain connotative meanings based on Leech's semantic theory (1981). The results show that connotative meanings in the movie’s dialogue not only function as language embellishments but also become the main source of energy in building dramatic atmosphere and the characters' inner conflicts. The connotations that emerge reflect the social, cultural, and emotional values of Javanese society, which is still bound by hierarchical structures and politeness. Through the use of symbol-laden language, this film presents a dramatization that not only evokes emotions but also provides a reflection of social reality.